Environmental risk factors for the development of oral squamous cell carcinoma in cats - Riccardo Zaccone; Andrea Renzi; Carmit Chalfon; Jacopo Lenzi; Emma Bellei; Laura Marconato; Eriberta Ros; Antonella Rigillo; Giuliano Bettini; Eugenio Faroni; Dina Guerra; Silvia Sabattini (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Risk factors for oral squamous cell carcinoma (OSCC) in cats are derived from a single study dated almost 20 years ago. The relationship between inflammation of oral tissues and OSCC is still unclear. Objectives To investigate previously proposed and novel potential risk factors for OSCC development, including oral inflammatory diseases. Animals Hundred cats with OSCC, 70 cats with chronic gingivostomatitis (CGS), 63 cats with periodontal disease (PD), and 500 controls. Methods Prospective, observational case‐control study. Cats with OSCC were compared with an age‐matched control sample of client‐owned cats and cats with CGS or PD. Owners of cats completed an anonymous questionnaire including demographic, environmental and lifestyle information. Results On multivariable logistic regression, covariates significantly associated with an increased risk of OSCC were rural environment (OR: 1.77; 95% CI: 1.03‐3.04; P = .04), outdoor access (OR: 1.68; 95% CI: 1.07‐2.63; P = .02), environmental tobacco smoke (OR: 1.77; 95% CI: 1.05‐3; P = .03), and petfood containing chemical additives (OR: 1.98; 95% CI: 1.04‐3.76; P = .04). Risk factors shared with CGS and PD were outdoor access and petfood containing chemical additives, respectively. A history of oral inflammation was reported in 35% of cats with OSCC but did not emerge as a risk factor. Conclusions and Clinical Importance The study proposes novel potential risk factors for OSCC in cats. Although a history of inflammatory oral disease was not significantly more frequent compared with random age‐matched controls, OSCC shared several risk factors with CGS and PD.